Cycloartane-type Triterpene Glycosides from the Rhizomes of Cimicifuga heracleifolia and Their Anticomplementary Activity - Lee, Jung Hoon; Cuong, To Dao; Kwack, Seung Jun; Seok, Ji Hyeon; Lee, Jong Kwon; Jeong, Ja Young; Woo, Mi-Hee; Choi, Jae Sue; Lee, Hyeong Kyu; Min, Byung Sun (Planta Medica, 2012)
Seven known triterpene glycosides, 23-O-acetylshengmanol 3-O-α-L-arabinopyranoside (1), 23-O-acetylshengmanol 3-O-β-D-xylopyranoside (2), 24-epi-24-O-acetylhydroshengmanol 3-O-β-D-xylopyranoside (3), cimiaceroside B (4), (23R,24S)-cimigenol 3-O-β-D-xylopyranoside (5), (23R,24R)-25-O-acetylcimigenol 3-O-β-D-xylopyranoside (6) and (23R,24S)-25-O-anhydrocimigenol 3-O-β-D-xylopyranoside (7) were isolated from the rhizomes of Cimicifuga heracleifolia. Their chemical structures were determined on the basis of spectroscopic analyses including 2D NMR. All isolates were investigated for their inhibitory effects on the classical pathway of the complement system. Among them, compound 6 showed strong inhibitory activity with an IC50 value of 7.7 µM while compound 3 was moderately active with an IC50 value of 195.6 µM.
Keywords: Cimicifuga heracleifolia; Ranunculaceae; cycloartane glycoside; anticomplement activity